KAJIAN DAMPAK EKONOMI PEMBENTUKAN KAWASAN EKONOMI KHUSUS - Tumpal Sihaloho; Naufa Muna (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2010)
The purpose of this study was to identify problems in the economic area and to analyze the impact of the establishment of Special economic zones (Sez) on the growth of investment, trade and labor. This study used a qualitative descriptive analysis of the legal and institutional aspects, infrastructure and planning, as well as incentives and financing. This study also used the Incremental Capital Output Ratio analysis (ICOR), Output Ratio Incremental Labour (ILOR) and the Location Quotient (LQ) to 12 (twelve) areas that suggest themselves into KEK: Sumatera Utara, Riau, South Sumatera, Banten, West Java, Central Java, east Java, West Kalimantan, Central Kalimantan, east Kalimantan, South Sulawesi and Central Sulawesi. The results showed that the common problems faced by the economic area is the provision of incentives that are not in accordance with the conditions of the region, and the lack of consistency between the rules that become the foundation and establishment of economic zones and the supporting regulations. from this study it is known that West Java and Banten region has the potential economic impact that relatively better than other regions.